Association of anxiety status and anxiety duration with constipation in adult Americans: a cross-sectional study using data from the NHANES 2007–2010 - Xinran Li; Conghui Bian; Hui Dai; Xingrui Chen; Haihua Qian; Dan Zhang (BMC Gastroenterology)
Abstract Background Constipated patients may exhibit anxious behaviors, but the relationship between the two remains unclear. This population-based study aims to investigate the relationships of anxiety status and anxiety duration with constipation among U.S. adults. Methods Using data from the National Health and Nutrition Examination Survey (NHANES) database spanning from 2007 to 2010, a cross-sectional study included 8945 participants was performed to assess the relationships of anxiety status and anxiety duration with constipation. Participants’ characteristics were presented using mean or proportion. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using multivariable logistic regression models. The analysis accounted for potential confounding factors, including gender, age, race/ethnicity, education level, marital status, PIR, BMI, smoking status, drinking status, chronic diseases, and dietary intake. Subgroup analyses were conducted to ensure the stability of the results. Smoothed curve fitting was applied to investigate both linear and nonlinear associations between anxiety duration and constipation risk. Threshold effects were assessed using two-piecewise linear regression models. Results Of the 8945 participants, 922 reported constipation, with a prevalence of 10.3%. After adjusting for confounding factors, individuals with anxiety status exhibited an increased risk of constipation (OR: 1.49, 95% CI: 1.28–1.73). Stratified analyses indicated that the association between anxiety status and constipation remained relatively stable across different stratification levels. Smoothed curve fitting and threshold effect analyses revealed a linear association between anxiety duration and constipation among adults aged 20–60, while a nonlinear inverted U-shaped relationship was observed in those aged 60 and older, with an inflection point at 10 days. The two variables correlated positively on the left side of the inflection point but not on the right. Conclusion This study showed that a significant association between anxiety status and constipation among U.S. adults. Additionally, an age-dependent association between anxiety duration and constipation was observed, particularly among individuals aged 60 and older.